The Anticancer Activity for the Bumetanide-Based Analogs via Targeting the Tumor-Associated Membrane-Bound Human Carbonic Anhydrase-IX Enzyme - Azizah M. Malebari; Tarek S. Ibrahim; Ibrahim M. Salem; Ismail Salama; Ahdab N. Khayyat; Samia M. Mostafa; Osama I. El-Sabbagh; Khaled M. Darwish (MDPI AG, 2020)
The membrane-bound human carbonic anhydrase (hCA) IX is widely recognized as a marker of tumor hypoxia and a prognostic factor within several human cancers. Being undetected in most normal tissues, hCA-IX implies the pharmacotherapeutic advent of reduced off-target adverse effects. We assessed the potential anticancer activity of bumetanide-based analogues to inhibit the hCA-IX enzymatic activity and cell proliferation of two solid cancer cell lines, namely kidney carcinoma (A-498) and bladder squamous cell carcinoma (SCaBER). Bumetanide analogues efficiently inhibit the target hCA-IX in low nanomolar activity (IC50 = 4.4-23.7 nM) and have an excellent selectivity profile (SI = 14.5-804) relative to the ubiquitous hCA-II isoform. Additionally, molecular docking studies provided insights into the compounds' structure-activity relationship and preferential binding of small-sized as well as selective bulky ligands towards the hCA-IX pocket. In particular, 2,4-dihydro-1,2,4-triazole-3-thione derivative 9c displayed pronounced hCA-IX inhibitory activity and impressive antiproliferative activity on oncogenic A-498 kidney carcinoma cells and is being considered as a promising anticancer candidate. Future studies will aim to optimize this compound to fine-tune its anticancer activity as well as explore its potential through in-vivo preclinical studies.